On the psychological analysis of visual perceptive search - Gučas , A.; Rimkutė , E. (Psichologija, 1971)
Mathematical description of information search imposes some restrictions. After quantitative and qualitative analysis of cyclograms of traces of eye-movement in film (given shape must have been traced in task A where the search field consists of randomly placed individual shapes, and task B where the searched shape is an element of a complex field structure) exposes specific factors which are usually not taken into account in mathematical models. Of those stand out particularly subject efforts to shorten the search time, certainty in decision-making, subtle time dosage in tracing indifferent field elements etc. Only in 40% of cases the decision was made when the gaze was fixed onto the shape in search. The duration of fixation (in seconds) before fixing the gaze onto A – 0,22, B – 0,29. In all other cases the trajectory of eye movements over the shape in search ends only in repeated fixations (25%) or the search discontinues on indifferent field (25%). The mean duration of fixations on the shape in search is A-0,32, B – 0,44, and on indifferent field A – 0,19, B – 0,32.